2020
DOI: 10.3390/agronomy10050644
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and Economic Evaluation of Autumn Planted Sugarcane under Different Planting Patterns with Lentil Intercropping

Abstract: Proper sowing orientation and spacing are important factors for best crop growth. A field experiment was conducted to study the effect of different planting patterns with and without lentil intercropping on sugarcane growth and yield and farm economics. Each of these treatments were planted as sole crop and intercropped with lentil. Data were collected on plant cane and first ratoon crop. The maximum stripped cane yields (154.36 t/ha and 130.28 t/ha in plant and ratoon crop, respectively) were obtained from su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…"After sugarcane emergence (5-6 weeks), it remains dormant for 3-4 months due to low temperature. To drive benefits from its slow growth and better use of resources, intercropping of some short-duration crops (leguminous crops) can be explored" [17,18]. Some studies have shown that "a legume intercropping system can induce legumes to fix more atmospheric N 2 by increasing competition with neighboring intercropped crops" [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"After sugarcane emergence (5-6 weeks), it remains dormant for 3-4 months due to low temperature. To drive benefits from its slow growth and better use of resources, intercropping of some short-duration crops (leguminous crops) can be explored" [17,18]. Some studies have shown that "a legume intercropping system can induce legumes to fix more atmospheric N 2 by increasing competition with neighboring intercropped crops" [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the potential of sugarcane intercropping with pulses such as soybean (Teshome et al 2016; Shimming & Gliessman, 2015) [23], common bean [24], cowpea, and white lupin [25], lentil [17]; oil seeds such as rapeseed and mustard seed [26]; cereals such as maize (Pillay and Mamet, 2008). "Soybean (Glycine max L.) is currently the world's most important food protein source and hence crucial for food security.…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, ethanol is produced at a small scale in sugar industries and does not play a significant role in Pakistan's economy whereas 80% sugar is produced from it. However, at national level the average per hectare production of sugarcane is low due climate change (Nadeem et al, 2020;Zhao and Yang 2015). Climate change is one of the emerging issues in the world.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the management of planting density and spatial arrangement has a crucial role to play in reducing intra-and inter-specific competition for natural resources and external inputs. Nadeem et al [7] suggest the adoption of a 120 cm trench planting pattern, along with lentil intercropping for improved LER (land equivalent ratio), economic return and seed yield of sugarcane, as compared to other intercropping patterns and a control (sole cropping), likely due to the improved utilization of farming inputs and an increased lentil plant population. This positively influences variability in millable canes m −2 due to increased nutrient accessibility, better air circulation and interception of light, resulting in reduced shoot mortality and better growth of canes.…”
mentioning
confidence: 99%
“…Thus, it is crucial to establish how to effectively utilize fertilizers or to increase the nutrient use efficiency of crops to obtain high yields in a sustainable way. Comprehensive research conducted by Deng et al [7] elucidates the potential to improve hemp fiber yield by combining a proper NPK application rate with an adequate choice of planting density. Since increasing the P or N fertilization rate generates a positive effect on hemp yield, while increasing the K fertilization rate or planting density has a negative impact, the authors conclude that to obtain yields of hemp with high-quality fiber of greater than 2200 kg ha −1 , the optimal ranges for cultivation conditions are: 329,950-371,500 plants ha −1 , 251-273 kg N ha −1 , 85-95 kg P 2 O 5 ha −1 , and 212-238 K 2 O kg ha −1 .…”
mentioning
confidence: 99%